2004
DOI: 10.1242/dev.01291
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-A receptor-dependent and -independent signaling pathways in establishing mandibular identity

Abstract: The lower jaw skeleton is derived from cephalic neural crest (CNC) cells that reside in the mandibular region of the first pharyngeal arch. Endothelin-A receptor (Ednra) signaling in crest cells is crucial for their development, as Ednra–/– mice are born with severe craniofacial defects resulting in neonatal lethality. In this study, we undertook a more detailed analysis of mandibular arch development in Ednra–/– embryos to better understand the cellular and molecular basis for these defects. We show that most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
223
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 138 publications
(242 citation statements)
references
References 71 publications
17
223
0
2
Order By: Relevance
“…Further transformations about the hinge are seen with the targeted disruption of both the endothelin signaling pathway and its potential targets, the nested Dlx5 and Dlx6 genes (Kurihara et al, 1994;Clouthier et al, 1998;Yanagisawa et al, 1998;Acampora et al, 1999;Depew et al, 1999;Charite et al, 2001;Ruest et al, 2004). Dlx5 is expressed both in early head mesenchyme (mdBA1 CNC) and epithelia (e.g., the early anterior cephalic ectoderm, ANR, and olfactory and otic placodes; Simeone et al, 1994;Qiu et al, 1997;Yang et al, 1998;Depew et al, 1999).…”
Section: Figmentioning
confidence: 99%
“…Further transformations about the hinge are seen with the targeted disruption of both the endothelin signaling pathway and its potential targets, the nested Dlx5 and Dlx6 genes (Kurihara et al, 1994;Clouthier et al, 1998;Yanagisawa et al, 1998;Acampora et al, 1999;Depew et al, 1999;Charite et al, 2001;Ruest et al, 2004). Dlx5 is expressed both in early head mesenchyme (mdBA1 CNC) and epithelia (e.g., the early anterior cephalic ectoderm, ANR, and olfactory and otic placodes; Simeone et al, 1994;Qiu et al, 1997;Yang et al, 1998;Depew et al, 1999).…”
Section: Figmentioning
confidence: 99%
“…Indeed Edn1 is expressed in the endoderm and in the mesodermal core of the mandibular prominence of PA1, whereas Ednra (Edn1 receptor-type A) is broadly expressed by the CNCC-derived PA1 ectomesenchyme and Dlx5;Dlx6 are only expressed in the mesenchyme of the mandibular prominence (Abe et al, 2007;Clouthier et al, 1998Clouthier et al, , 2000Ozeki et al, 2004;Ruest et al, 2004Ruest et al, , 2005. Loss of Edn1?Ednra signaling results in the down regulation of the two members of the distalless homeobox gene family Dlx5 and Dlx6 (Merlo et al, 2002a;Panganiban and Rubenstein, 2002), and in a homeotic-like transformation of lower into upper jaw structures, similar to that observed upon double inactivation of Dlx5 and Dlx6 (Beverdam et al, 2002;Depew et al, 2002;Fukuhara et al, 2004;Ruest et al, 2004). The constitutive activation of the Edn1?Ednra signaling in the entire PA1 induces a partial transformation of the upper jaw suggesting that PA1 CNCCs are competent to respond to Edn1 signaling.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main aims of our study was to identify genes that could be used as markers of the different facial prominences. There are an increasing number of studies where genetic or molecular manipulations have resulted in dramatic homeotic transformations of the jaws (Miller et al, 2000;Lee et al, 2001;Kimmel et al, 2003Kimmel et al, , 2007Ruest et al, 2004;Sato et al, 2008). One difficulty in determining whether the molecular landscape of the transformed region is converted to the new identity is that it is difficult to find genes that are restricted to different regions of the face.…”
Section: Discussionmentioning
confidence: 99%
“…However, other targeting experiments in which the first branchial arch enhancer of Hand2 was selectively deleted showed major reductions in the mandible (Yanagisawa et al, 2003). Hand2 is in the pathway that controls mandibular identity (Depew et al, 2002;Ruest et al, 2004), but no changes in identity were observed in the enhancer knockout. Studies that investigate genetic interactions between Hand2 and Dlx5/6 or Ednra (Endothelin receptor A) may yet reveal a contributing role for Hand2 in specifying identity.…”
Section: Genes That Characterize the Mandibular Prominencesmentioning
confidence: 93%
See 1 more Smart Citation